- Factors affecting the decrease in demand for insurance service - Applied research in the National Insurance Company 2006 - 2015 - Al Baldawi, Alaa; Al Saadi, Khaled (Journal of Economic, Administrative and Legal Sciences, 2018)
There is no doubt that the volume of demand for insurance service, which is the premiums in the case of a clear decline, due to several reasons, including the reluctance of a large part of the Iraqi society for the request for insurance service as a result of economic factors and technical and legal impact. The study adopted the descriptive method in the identification and treatment of variables, (Per capita income, inflation, population distribution, individual insurance culture, promotional methods, laws and regulations) as independent variables and demand for insurance service as a dependent variable. For the purpose of achieving the research objectives, the researcher used the questionnaire to collect the data and information needed for the study, as well as the data available in the reports and statistics of the company and the Central Statistical Organization.
Keywords: factors; influencing; demand; insurance service; reduction